Etnografi Virtual Sandwich Generation melalui Lagu “Berakhir di Aku” di Media Sosial - Salimah H, Syelma Nur; Kurniawan, Achmad Wildan; Adnan, Iis Zilfah (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This research aims to examine how the song “Berakhir di Aku” by Idgitaf represent the emotional realities and struggles of Sandwich Generation, especially among Generation Z, and how the use of social media platforms TikTok and Instagram facilitates expression and interaction within this group. The study employs a qualitative descriptive method with a virtual ethnography approach, collecting data through virtual interviews, observation of social media content, and literature review. Data analysis is conducted using Cyber Media Analysis, which explores various levels of digital interaction. The findings indicate that “Berakhir di Aku” serves as a significant medium for emotional release and self-reflection, while TikTok and Instagram function as virtual spaces that support the process of self-acceptance through diverse forms of expression and communication among members of the Sandwich Generation. This study contributes by finding that social media is not only used as a means of entertainment, but has an important function as a space for emotional support and identity socialization, which facilitates the process of self-acceptance among members of the Sandwich Generation, through intense virtual interactions.